2017
DOI: 10.1186/s12891-017-1745-4
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of dietary gelatin hydrolysates on bone mineral density in magnesium-deficient rats

Abstract: BackgroundThe major types of commercially available gelatin hydrolysates are prepared from mammals or fish. Dietary gelatin hydrolysates from mammals were reported to improve bone mineral density (BMD) in some animal models. In contrast, there is limited study showing the effects of dietary gelatin hydrolysates from fish on BMD. The quantity and structure of peptides in the plasma after oral administration of gelatin hydrolysates depend on the gelatin source, which suggests that the biological activity of gela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Morphometric measurements were supportive to the histological findings; there was significant increase in the mean thickness of compact bone and in the mean area of trabecular bone when compared to FM groups (II and IV). This is in accordance with an earlier study, which investigated the effect of CH in magnesium deficient OP rats and proved that it could attenuate bone brittleness by increasing cortical thickness [2] . Similar finding was reported by Liu et al [21] who stated that CP supplementation could inhibit bone loss with significant increase in the trabecular bone area in ovariectomized OP rats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Morphometric measurements were supportive to the histological findings; there was significant increase in the mean thickness of compact bone and in the mean area of trabecular bone when compared to FM groups (II and IV). This is in accordance with an earlier study, which investigated the effect of CH in magnesium deficient OP rats and proved that it could attenuate bone brittleness by increasing cortical thickness [2] . Similar finding was reported by Liu et al [21] who stated that CP supplementation could inhibit bone loss with significant increase in the trabecular bone area in ovariectomized OP rats.…”
Section: Discussionsupporting
confidence: 93%
“…Osteoporosis (OP) is a globally growing health problem affecting over 200 million people worldwide and the annual incidence of hip fracture due to this disease is about 1.7 million worldwide [1] . It is characterized by deterioration of bone tissue and low bone mass because of enhanced bone resorption that is not compensated by enhanced bone formation, increasing fracture risk [2] . Primary OP is associated with aging and is more common in women especially postmenopausal due to decreased estrogen.…”
Section: Introductionmentioning
confidence: 99%
“…To support bone health, a number of studies focused on the supplementation of FPH to the individual have been carried out. In their study, Noma et al (2017) evaluated the effect of FPH (5%) on bone mineral density in magnesium (Mg)-deficient male Wistar rats in comparison with porcine gelatin hydrolysate (PGH, 5%) and control (48 mg Mg/100 g diet) during 8 weeks of feeding trial. The result showed that both FPH and PGH increase cortical thickness in Mg-deficient rats.…”
Section: Health Benefits Of Fph (In Vivo Studies)mentioning
confidence: 99%
“…Another study was conducted by Norma, in which fish gelatin was used to minimise the bone brittleness. The results showed that fish gelatin has huge potential in order to attenuate the bone brittleness (Noma et al ., 2017). Fish gelatin could be utilised as a potential anti‐hypertensive agent in the diet of people who are affected by hypertensive condition which is a major risk for cardiovascular diseases (Kearney et al ., 2005; Chen et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%